Human Umbilical Cord-Derived Mesenchymal Stem Cell Therapy Ameliorates Nonalcoholic Fatty Liver Disease in Obese Type 2 Diabetic Mice. (3rd November 2019) - Li, Bing; Cheng, Yu; Yu, Songyan; Zang, Li; Yin, Yaqi; Liu, Jiejie; Zhang, Lin; Mu, Yiming
Abstract : Nonalcoholic fatty liver disease (NAFLD) is increasingly common among patients with type 2 diabetes mellitus (T2DM). The two conditions can act synergistically to produce adverse outcomes. However, the therapeutic options for patients with NAFLD and T2DM are currently limited. Human umbilical cord-derived mesenchymal stem cells (UC-MSCs) have shown therapeutic potential for diabetes and hepatic disorders such as liver cirrhosis and fulminant hepatic failure. The present study is aimed at investigating the effect of human UC-MSCs on a mouse model of NAFLD and T2DM, characterized by obesity-induced hyperglycaemia, dyslipidaemia, hepatic steatosis, and liver dysfunction. Thirty-week-old male C57BL/6 db/db mice were infused with human UC-MSCs or phosphate-buffered saline (PBS) via the tail vein once a week for six weeks. Age-matched male C57BL/6 wild-type db/+ mice were used as controls. Body weight and random blood glucose were measured every week. One week after the sixth infusion, intraperitoneal glucose tolerance tests and insulin tolerance tests were performed and the blood and liver were harvested for biochemical and histopathological examinations. Quantitative real-time reverse transcriptase polymerase chain reaction (qRT-PCR), immunofluorescence staining, and western blot were performed to monitor the expression of the lipid metabolism- and regulatory pathway-related genes. UC-MSC infusions significantly ameliorated hyperglycaemia, attenuated the elevation of hepatic transaminases, and decreased lipid contents, including triglyceride, total cholesterol, and low-density lipoprotein cholesterol. Moreover, histological lesions in the liver diminished markedly, as evidenced by reduced lipid accumulation and attenuated hepatic steatosis. Mechanistically, UC-MSCs were found to regulate lipid metabolism by increasing the expression of fatty acid oxidation-related genes and inhibiting the expression of lipogenesis-related genes, which were associated with the upregulation of the HNF4 α -CES2 pathway. Our results demonstrate that human UC-MSCs can ameliorate NAFLD and reverse metabolic syndrome in db/db mice. Thus, UC-MSCs may serve as a novel therapeutic agent for T2DM patients with NAFLD.